2018
DOI: 10.1002/alr.22073
|View full text |Cite
|
Sign up to set email alerts
|

International Consensus Statement on Allergy and Rhinology: Allergic Rhinitis

Abstract: This critical review of the AR literature has identified several strengths; providers can be confident that treatment decisions are supported by rigorous studies. However, there are also substantial gaps in the AR literature. These knowledge gaps should be viewed as opportunities for improvement, as often the things that we teach and the medicine that we practice are not based on the best quality evidence. This document aims to highlight the strengths and weaknesses of the AR literature to identify areas for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
453
0
35

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 339 publications
(520 citation statements)
references
References 1,903 publications
8
453
0
35
Order By: Relevance
“…In addition, no difference was observed between the two drugs regarding safety and tolerability. Considering that the most common complaint of patients with AR is nasal congestion, rated as “extremely bothersome” [8, 19], a validated efficacy assessment for such drugs is the rTNSS outcome as evaluated in this trial [6]. Both sprays decreased rTNSS values from baseline to the end of study treatment with a mean difference of 0.2 (95% CI –0.89 to 0.54) between the two treatment groups, with the upper CI limit being less than the stated non-inferiority margin of 0.8, confirming that triamcinolone acetonide is non-inferior to fluticasone propionate with respect to symptom control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, no difference was observed between the two drugs regarding safety and tolerability. Considering that the most common complaint of patients with AR is nasal congestion, rated as “extremely bothersome” [8, 19], a validated efficacy assessment for such drugs is the rTNSS outcome as evaluated in this trial [6]. Both sprays decreased rTNSS values from baseline to the end of study treatment with a mean difference of 0.2 (95% CI –0.89 to 0.54) between the two treatment groups, with the upper CI limit being less than the stated non-inferiority margin of 0.8, confirming that triamcinolone acetonide is non-inferior to fluticasone propionate with respect to symptom control.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmark of AR is an immunoglobulin E-mediated type 1 hypersensitivity reaction to an inciting inhaled seasonal or perennial allergen, triggering a cascade of immunological and biochemical events leading to clinical expression of the disease [6]. Thus, patients with AR exhibit signs of rhinorrhea, congestion, nasal itching, and obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…The nasal cavity is also home to a diverse group of fungi [4] and viruses [23]. It is noteworthy that both fungi and viruses can affect the nasal bacterial microbiome and trigger the immune system [22].…”
Section: Concerns and Areas Of Unmet Research Needs In The Nasal Micrmentioning
confidence: 99%
“…While commensal microorganisms and their metabolites maintain the stability of their habitat in a symbiotic system, disturbances in the composition of these commensal resident microbes and pathogens play important roles in the initiation and potentially the progression of inflammation [1]. Current research has shown evidence for dysbiosis of the nasal microbiome in the context of allergic and inflammatory diseases of the airways such as allergic rhinitis (AR) [2][3][4], chronic rhinosinusitis (CRS) [1,5,6], and asthma [7]. We also know that the effect of the microbiome is not confined to its immediate location but rather can affect the entire host physiology.…”
mentioning
confidence: 99%
“…As the allergy practitioner, researcher, or academician evaluates the literature, it is critical to understand the strength and quality of the evidence to allow for appropriate translation to daily clinical care in AR. The International Consensus Statement on Allergy and Rhinology: Allergic Rhinitis (ICAR:AR) 1 was developed to summarize and critically review the best external evidence in the realm of AR. This includes broad categories of epidemiology, risk factors, diagnosis, management, and associated conditions/comorbidities related to AR.…”
Section: Introductionmentioning
confidence: 99%